DEVELOPMENT OF GRAMMAR IN WRITTEN DISCOURSE E-BOOK WITH MULTIMODAL APPROACH USING BOOK-CREATOR APPLICATION - Hikmah Pravitasari; Nurul Afiyattena (Wiralodra English Journal, 2022)
The purpose of this research was to design and develop teaching material in the form of an electronic book using the Book Creator application for the Grammar in Written Discourse course. Design-based research was the method chosen which had 4 stages, namely problem identification and need analysis, program prototype development, testing and implementation, and reflection to obtain the expected design principles and overcome various problems that arise. This research was taken at a private university in Indonesia. There were 50 students voluntarily participating in this study. The data was collected from questionnaires, individual interviews, focused-group discussions, and document analyses. The research data were analyzed qualitatively and quantitatively. The findings revealed that students felt so enthusiastic with the presence of this grammar in written discourse E-book as their handbook which uses multimodal approach moreover the use of the multimodal approach in this E-book not only can assist students’ comprehension but also dig and train students’ autonomous learning. The findings and the design-based research approach adopted are applicable to tertiary students in other educational contexts as well as other areas of research interest.